Safety and efficacy of switching from low molecular weight heparin to dabigatran in patients undergoing elective total hip or knee replacement surgery. Issue 1 (December 2015) - Wurnig, Christian; Clemens, Andreas; Rauscher, Helmuth; Kleine, Eva; Feuring, Martin; Windhager, Reinhard; Grohs, Josef
Abstract Background The aim of this study was to assess the safety and efficacy of switching therapy from low molecular weight heparin (LMWH; enoxaparin) to dabigatran for prevention of venous thromboembolic events (VTE) in patients undergoing elective total hip or knee replacement surgery (THR/TKR). Methods This was a prospective, multicenter, open-label, single-arm, observational, study in patients undergoing THR or TKR who were to receive enoxaparin 40 mg for thromboprophylaxis. Enoxaparin was initiated before or after surgery according to local practice, and was switched to dabigatran 220 mg once daily at a time point chosen by the investigator. The coprimary endpoints were major bleeding events, and the composite of symptomatic VTE and all-cause mortality, from last use of enoxaparin to 24 h after last intake of dabigatran. Results Altogether, 168 (81 THR, 87 TKR) patients were enrolled, of whom 161 received both enoxaparin and dabigatran, 2 received dabigatran only and 5 received enoxaparin only. The median time of the first dabigatran tablet was 24.0 h after the last LMWH dosage and the median number of days on dabigatran treatment was 36 days. No symptomatic VTE or death occurred during the study. One major bleeding event was seen at the surgical site and required treatment cessation. Three minor bleeding events were observed. Conclusions In the normal clinical setting, switching from LMWH to dabigatran in patients who had undergone THR and TKR was safe and effective in preventing VTE. The reported adverse events and serious adverse events were consistent with the known safety profile for dabigatran. Switching from a subcutaneous to an oral anticoagulant may offer greater convenience in the outpatient setting after discharge. Trial registration ClinicalTrials.gov identifierNCT01153698 .